2021
DOI: 10.1038/s41420-021-00664-0
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0011385 knockdown represses cell proliferation in hepatocellular carcinoma

Abstract: Circular RNAs (circRNAs), continuous loops of single-stranded RNA, regulate gene expression during the development of various cancers. However, the function of circRNAs in hepatocellular carcinoma (HCC) is rarely discussed. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to determine the mRNA levels of circ_0011385, miR-361-3p, and STC2 in 96 pairs of HCC tissues (tumor tissues and adjacent normal tissues), HCC cell lines, and L02 (human normal liver cell line) cells. The relationships betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…circ_0006089 sponged miR-361-3p to regulate TGFB1, thereby promoting GC cell proliferation, metastasis, glycolysis, angiogenesis, and decreasing apoptosis inhibited miR-361-3p to promote hepatocellular carcinoma proliferation. 25 miR-361-3p had been determined to be a tumor suppressor in cervical cancer, which could suppress cancer cell viability and metastasis. 26 Many research confirmed that miR-361-3p exerted suppressive effects on GC cell growth and metastasis, as well as angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…circ_0006089 sponged miR-361-3p to regulate TGFB1, thereby promoting GC cell proliferation, metastasis, glycolysis, angiogenesis, and decreasing apoptosis inhibited miR-361-3p to promote hepatocellular carcinoma proliferation. 25 miR-361-3p had been determined to be a tumor suppressor in cervical cancer, which could suppress cancer cell viability and metastasis. 26 Many research confirmed that miR-361-3p exerted suppressive effects on GC cell growth and metastasis, as well as angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Here, miR‐361‐3p was confirmed to be sponged by circ_0006089. Studies had indicated that circ_0011385 inhibited miR‐361‐3p to promote hepatocellular carcinoma proliferation 25 . miR‐361‐3p had been determined to be a tumor suppressor in cervical cancer, which could suppress cancer cell viability and metastasis 26 .…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs have been demonstrated to play an essential role in the initiation and progression of multiple diseases, such as hypertension ( 18 20 ), cardiopathy ( 21 ), diabetes ( 22 ), and cancers ( 23 25 ). In hypertension, hsa_circ_0038648 has been found to be highly expressed in human aortic smooth muscle cells (HASMCs) and act as an independent risk factor for essential hypertension ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence has demonstrated that dysregulation of circRNAs plays critical roles in HCC tumorigenesis and progression through regulating key tumor regulatory genes. In view of the great importance of circRNAs in HCC, we previously revealed that circ_0011385 enhances HCC cell proliferation and tumor activity via regulation through the miR-361-3p/STC2 axis and that circCRIM1 facilitates HCC progression and angiogenesis by sponging miR-378a-3p ( 9 , 11 ). Owning to the circular structures, circRNAs are more stable than the corresponding linear forms and are expected to be exciting targets for tumor drug discovery ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the development of next-generation sequencing of noncoding RNAs, a growing number of circRNAs have been found play important roles in cancer cell proliferation, metastasis, and treatment resistance by functioning as microRNA (miRNA) sponges and RNA-binding proteins ( 6 8 ). For instance, our group previously reported that circ_0011385 promoted HCC cell proliferation and was associated with poor clinicopathologic features ( 9 ). A recent study showed that hsa_circ_0001492 (circERBIN), originating from exons 2, 3, and 4 of the Erbin gene (ERBB2 inter-acting protein), promoted the proliferation and metastasis of colorectal cancer cells via targeting miR-125a-5p-5p/miR-138-5p to subsequently increase the expression of eukaryotic translation initiation factor 4E binding protein 1 and translation of hypoxia induced factor-1 ( 10 ).…”
Section: Introductionmentioning
confidence: 99%